Frequency of Metabolic Syndrome in Patients With Ischemic Stroke - Khan, Naeem; Shehzad, .; Bilal, Muhammad; Hanan, Abdul; Khan, Aamir; Yasir, . (Biological and Clinical Sciences Research Journal, 2025)
Stroke is the second-leading cause of mortality globally and metabolic syndrome is considered a distinct risk factor for stroke. Objective: The aim this study was to determine the frequency of metabolic syndrome in patients with ischemic stroke. Method: The current cross-sectional study was conducted in Qazi Hussain Ahmad Medical Complex, Nowshera, over 6 months after taking approval from the CPSP and ethical board of the institute from 2nd July 2024 to 2nd January 2025. A total of 145 individuals of both gender and different age groups (30-70 years) diagnosed with ischemic stroke were included. Demographic features such as age, gender, occupation, BMI socio economic status, smoking history and residency were recorded. Individuals with ischemic stroke were examine for metabolic syndrome which were labeled positive based on the 3 criteria that are triglycerids level ≥ 150mg/dl, HDL level ≤ 40mg/dl in males and ≤ 50mg/ dl in females ,hypertension (blood pressure ≥ 130/85) and diabetes Fasting blood glucose ≥ 126mg/d. Data was analyzed through SPSS version 21.0. The Shapiro-Wilk test was used to determine the uniformity of the continuous data. Ages, height, weight, body mass index & the duration of acute ischemic stroke were calculated using mean, SD, or median (with IQR). Chi-square and Fisher exact tests were employed to assess the significance of study parameter proportions across courses. A p-value less than 0.05 was regarded as statistically significant. Results: A total of 145 individuals with ischemic heart disease were enrolled in this study out of which 102(70.3%) were male and 43(29.6%) were females. Metabolic syndrome was identified in 72(50%) individuals. Gender significantly correlates with metabolic syndrome (P < 0.05). The mean triglyceride level was 1151.36±17.8 mg/dL, HDL level was 45.6±5.9 mg/dL and fasting blood glucose level was 118.6 ± 38.4 mg/dL. The most common components were hypertension and low HDL, which were positive in 85 (58.6%), followed by diabetes & elevated triglycerides levels in 66 (45.5%) and 58 (40%). Conclusion: Our study concluded that metabolic syndrome is a major risk factor for ischemic stroke.